South China Sea Conflict and Indonesia's Strategy Toward Indonesia Emas 2045 - Ras, Abdul Rivai; Soemantri, Asep Iwa; Asih Yulianto, Bayu; Yudho Prakoso, Lukman; Risahdi, Muhammad (Jurnal Indonesia Sosial Sains, 2025)
The South China Sea (SCS) is a strategically vital maritime area, rich in resources and international trade routes, yet prone to territorial disputes. Although Indonesia does not claim the SCS, it faces challenges regarding the Natuna Sea Exclusive Economic Zone (EEZ) due to unilateral claims by China. This study analyzes the dynamics of the SCS conflict and Indonesia’s strategies toward achieving Indonesia Emas 2045 through strengthened maritime security, diplomacy, and resource management. A qualitative descriptive method with document and statistical data analysis is applied. Findings indicate that maritime surveillance, defense modernization, and multilateral cooperation are essential to safeguarding sovereignty and enhancing Indonesia’s regional position.